Identification, Mapping, and Molecular Marker Development for Rgsr8.1: A New Quantitative Trait Locus Conferring Resistance to Gibberella Stalk Rot in Maize (Zea mays L.) - Chen, Qian; Song, Jun; Du, Wen-Ping; Xu, Li-Yuan; Jiang, Yun; Zhang, Jie; Xiang, Xiao-Li; Yu, Gui-Rong (Frontiers in Plant Science, 2017)
Maize stalk rot is a major fungal disease worldwide, and is difficult to control by chemical methods. Therefore, in maize breeding, quantitative trait loci (QTLs) conferring resistance are important for controlling the disease. Next-generation sequencing technologies are considered a rapid and efficient method to establish the association of agronomic traits with molecular markers or candidate genes. In the present study, we employed QTL-seq, which is a whole-genome resequencing-based approach, to identify candidate genomic regions conferring resistance to maize stalk rot. A novel resistance QTL Rgsr8.1 was finely mapped, conferring broad-spectrum resistance to Gibberella stalk rot (GSR). Segregation analysis in F2 and BC1F1 populations, which were derived from a cross between 18327 (Susceptible) and S72356 (Resistant), indicated that the resistance to GSR was likely to be a quantitatively inherited trait in maize. The result of QTL-seq showed that the resistance to GSR was mapped on chromosome 8 from 161.001 to 170.6 Mb. Based on the simple sequence repeat (SSR) markers, single nucleotide polymorphism (SNP) markers, and the recombinant test, the location of Rgsr8.1 was narrowed down to 2.04 Mb, flanked by SSR-65 and SNP-25 markers at the physical location from 164.69 to 166.72 Mb based on the Maize reference genome. In this region, two candidate resistant genes were found with, one auxin-responsive elements and the other encoding a disease resistance protein. In summary, these results will be useful in maize breeding programs to improve the resistance to GSR in maize.